2017
DOI: 10.1080/03007995.2016.1277197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost implications of amyloid beta detection with amyloid beta positron emission tomography imaging in early Alzheimer’s disease – the case of florbetapir

Abstract: Aβ-PET is projected to affordably increase QALYs from the French HTA perspective per guidance over a range of clinical scenarios, comparators, and input parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 59 publications
0
54
1
Order By: Relevance
“…AD patients rated as Aβ positive showed a similar pattern on measures of global cognition and verbal fluency(Doraiswamy et al, 2014). When considering the clinical implementation of this modality, recent evidence demonstrates its cost-effectiveness(Hornberger, Bae, Watson, Johnston, & Happich, 2017) and meaningful impact on the diagnostic confidence for AD by physicians(Boccardi et al, 2016).While not as widely investigated as [ 18 F]florbetapir, a similar pattern of amyloid retention is demonstrated throughout the cortex in AD using both [ 18 F]florbetaben(Barthel et al, 2011) and [ 18 F] flutemetamol(Nelissen et al, 2009). When considering the clinical implementation of this modality, recent evidence demonstrates its cost-effectiveness(Hornberger, Bae, Watson, Johnston, & Happich, 2017) and meaningful impact on the diagnostic confidence for AD by physicians(Boccardi et al, 2016).While not as widely investigated as [ 18 F]florbetapir, a similar pattern of amyloid retention is demonstrated throughout the cortex in AD using both [ 18 F]florbetaben(Barthel et al, 2011) and [ 18 F] flutemetamol(Nelissen et al, 2009).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…AD patients rated as Aβ positive showed a similar pattern on measures of global cognition and verbal fluency(Doraiswamy et al, 2014). When considering the clinical implementation of this modality, recent evidence demonstrates its cost-effectiveness(Hornberger, Bae, Watson, Johnston, & Happich, 2017) and meaningful impact on the diagnostic confidence for AD by physicians(Boccardi et al, 2016).While not as widely investigated as [ 18 F]florbetapir, a similar pattern of amyloid retention is demonstrated throughout the cortex in AD using both [ 18 F]florbetaben(Barthel et al, 2011) and [ 18 F] flutemetamol(Nelissen et al, 2009). When considering the clinical implementation of this modality, recent evidence demonstrates its cost-effectiveness(Hornberger, Bae, Watson, Johnston, & Happich, 2017) and meaningful impact on the diagnostic confidence for AD by physicians(Boccardi et al, 2016).While not as widely investigated as [ 18 F]florbetapir, a similar pattern of amyloid retention is demonstrated throughout the cortex in AD using both [ 18 F]florbetaben(Barthel et al, 2011) and [ 18 F] flutemetamol(Nelissen et al, 2009).…”
mentioning
confidence: 93%
“…Moreover, a positive amyloid scan for MCI patients indicates a greater risk of disease progression to AD.While 18 F-labelled amyloid tracers are equivalent in their degree of diagnostic accuracy, [ 18 F]florbetapir shows particularly fast brain kinetics relative to others(Wong et al, 2010). When considering the clinical implementation of this modality, recent evidence demonstrates its cost-effectiveness(Hornberger, Bae, Watson, Johnston, & Happich, 2017) and meaningful impact on the diagnostic confidence for AD by physicians(Boccardi et al, 2016).While not as widely investigated as [ 18 F]florbetapir, a similar pattern of amyloid retention is demonstrated throughout the cortex in AD using both [ 18 F]florbetaben(Barthel et al, 2011) and [ 18 F]…”
mentioning
confidence: 99%
“…Sixteen studies concerning the clinical utility of amyloid PET imaging were found in the literature (17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Supplemental Table 3 summarizes these studies.…”
Section: Clinical Utility Of Amyloid Imagingmentioning
confidence: 99%
“…Also, in the predementia group, amyloid imaging was associated with a better outcome regarding duration of the predementia phase, caregiver time, and other parameters. Hornberger et al (43,48) performed 2 similar simulations for 18 F-florbetapir PET in Spanish and French dementia cohorts. The QALY gains by amyloid imaging (likewise as compared with a scenario without amyloid imaging) estimated in these modeling studies were 0.008 and 0.021, respectively.…”
Section: Impact Of Amyloid Imaging On Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation